Hak-Hak Politik Warga Negara non Muslim sebagai Pemimpin dalam Pandangan Hukum Islam dan Hukum Positif - Dudi Badruzaman (Jurnal Supremasi, 2019)
Leaders are very important in a country, in the life of the state the community has political rights such as the right to choose and be elected. however, regarding the chosen rights of non-Muslims as leaders, it became a controversy in Islamic law because of the differences of opinion between classical scholars and contemporary ulama for that there needs to be a detailed discussion about the ability of a non-Muslim to become a leader. the formulation of the problem in this study is how the political rights of non-Muslim citizens in the view of Islamic law and positive law, and whether there are differences and similarities in the political rights of non-Muslim citizens in the view of Islamic law and positive law. The research method that the author did was LibraryResearch research with a normative approach and legal comparison method. The technique of data collection is done by studying the literature sourced from the 1945 Constitution, Law, Al-Qur'an, Hadith and opinions of scholars and legal experts in Indonesia. At the stage of data analysis, data is processed and utilized in such a way as to be able to deduce truths that can be used to answer the problems in this study.